2020
DOI: 10.1002/adfm.202007564
|View full text |Cite
|
Sign up to set email alerts
|

3D Imaging of Lithium Protrusions in Solid‐State Lithium Batteries using X‐Ray Computed Tomography

Abstract: Solid‐state lithium batteries will revolutionize the lithium‐ion battery and energy storage applications if certain key challenges can be resolved. The formation of lithium‐protrusions (dendrites) that can cause catastrophic short‐circuiting is one of the main obstacles, and progresses by a mechanism that is not yet fully understood. By utilizing X‐ray computed tomography with nanoscale resolution, the 3D morphology of lithium protrusions inside short‐circuited solid electrolytes has been obtained for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 38 publications
(65 reference statements)
2
35
0
Order By: Relevance
“…It is noted that a recent experimental study using X‐ray computed tomography with nanoscale resolution has also observed preferential intergranular penetration of Li filaments and metal‐filled cracks that formed a waved plane in the shape of GBs within LLZO. [ 33 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that a recent experimental study using X‐ray computed tomography with nanoscale resolution has also observed preferential intergranular penetration of Li filaments and metal‐filled cracks that formed a waved plane in the shape of GBs within LLZO. [ 33 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that a recent experimental study using X-ray computed tomography with nanoscale resolution has also observed preferential intergranular penetration of Li filaments and metal-filled cracks that formed a waved plane in the shape of GBs within LLZO. [33] Compared to the metal penetration mechanism explained above, the mode of failure is quite different in case of an ionically more conductive GB, as compared to the grains. Due to an escalation in the ion occupation of GBs that was described in the previous section, preferential nucleation occurs at the GB-electrode interface as shown in Figure 5a.…”
Section: Electrochemical-mechanical Response Of the Solid Electrolytementioning
confidence: 92%
“…The use of a synchrotron source for CT yields further advantages, as X‐ray beams can be focused using a lens to achieve higher spatial resolution (e.g., 30 nm or less), and the high intensity from synchrotron enables fast data collection with better temporal resolution 136,137 . This so‐called nano‐CT has been utilized to study SSEs, in particular, interfacial morphological changes.…”
Section: In Situ Imaging Of Solid–solid Interfacesmentioning
confidence: 99%
“…For example, the formation of lithium dendrites can cause catastrophic short‐circuiting, but is hard to observe due to weak diffraction from lithium. Paul Shearing's group 136,137 utilized synchrotron‐based in situ nano‐CT to directly visualize the 3D morphological evolution of cracks with deposited lithium as they penetrated through the solid electrolyte, LLZO, during repetitive plating. Although lithium is transparent to X‐ray, the cracks induced by the lithium protrusions can be quantified and analyzed statistically in the series of tomographic images.…”
Section: In Situ Imaging Of Solid–solid Interfacesmentioning
confidence: 99%
“…Synchrotron microtomography with phase contrast has been utilized to conduct operando imaging of lithium cells with liquid electrolyte, , with polymer electrolyte, and with solid-state electrolyte . The nondestructive nature of the X-ray tomographic approach facilitates the roughness investigation of the buried lithium-to-separator, lithium-to-polymer-electrolyte, and lithium-to-solid-state-electrolyte interfaces. , More recently, this method was also used to image the development of microcracks in the solid-state electrolyte, which is then followed by the infiltration of the lithium dendrites. Implemented with X-ray optics, the X-ray nanotomography with Zernike phase contrast was employed to image the 3D morphology of lithium metal electrodes that were cycled at different current densities and under different temperatures. , Pan et al utilized laboratory X-ray micro CT with a liquid metal jet source to image the micromorphology of lithium deposits and to correlate it with the electrochemical signal that was acquired concurrent with the tomographic scans . Collectively, these efforts not only highlight the strong enthusiasm in researching lithium but also reflect the immense challenges in this pursuit.…”
Section: Tricontrast X-ray Radiography On a Capillary Lithium Cellmentioning
confidence: 99%